Nursing Management of Language Barriers in Clinical Care - Shayiz Musaad Shayiz Alruwaili; Alruwaili, Abdulrahman Nawi; Alrowili, Fraiha Maazar S; Waili, Zahed Abdulhadi M; Hayfa Mashl Humid Alshammari; Hamdeah Radhi Alhazmi; Nawal Assam Wadi Alaenzi; Bashayr Salem H Alanazi; Majidah Fayadh G Alanazy; Eidah Mutlaq Alshammari; et al. (International Journal of Computational and Experimental Science and Engineering, 2024)
Effective communication is fundamental in healthcare, and language barriers can significantly hinder this process, impacting patient outcomes and satisfaction. Nurses play a critical role in managing these barriers by utilizing various strategies to ensure that patients with limited English proficiency (LEP) receive appropriate care. This includes employing professional medical interpreters, utilizing translation technology, and providing bilingual materials whenever possible. Additionally, nurses can receive training in cultural competence to enhance their understanding of diverse populations and their unique communication needs, fostering a more inclusive healthcare environment. Moreover, the establishment of a patient-centered care model is essential in addressing language barriers. Nurses are encouraged to engage patients actively in their care discussions, using visual aids and simplified language to facilitate understanding. By implementing routine screenings for language proficiency and offering resources such as language classes or community support services, nurses can empower patients to advocate for their own health effectively. Ultimately, overcoming language barriers not only improves clinical outcomes but also enhances the overall patient experience, demonstrating the integral role nurses play in bridging communication gaps within diverse patient populations.